Achieving distribution equity through emotional functionalities and value-based bonding: An analysis with structural equation modeling. Issue 1 (2nd January 2016) - Bhattachary, Subhajit; Singh, Anurag
Abstract: In the current competitive situation, distribution channels play an important role to create and develop a value-based setup in which companies can easily pipeline their products into the market. The distribution channels and their efficiencies are dependent on relationship bonding between channel partners and the company, backed by company value-sharing policies. Both emotional functionalities and tangible functional value play key roles in the success of distribution channel management. The current research is a thoughtful attempt to develop a framework to understand and explore the linkages among emotional linkage, tangible functional value and the value-based channel nexus to strengthen channel-based distribution equity. A total of 156 direct responses from channel members were collected from the FMCG industry across business territories of eastern India. The empirical data was analysed with structural equation modeling. The findings of the current research article illustrate a novel approach to manage a marketing distribution channel to create a higher level of emotional connectivity and engagement between the company and distribution channel partner. This would lead to the creation of channel-based distribution equity in the FMCG industry.